A core-satellite nanocomposite containing magnetic iron oxide coated with gold nanoparticles and method for manufacturing the same

KR103013736B1Active Publication Date: 2026-09-02THE IND & ACADEMIC COOP IN CHUNGNAM NAT UNIV (IAC)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
KR1020230185690
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-12-19
Publication Date
2026-09-02
Estimated Expiration
2043-12-19

Smart Images

  • Figure 112023142429258-PAT00001_ABST
    Figure 112023142429258-PAT00001_ABST
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing a core-satellite nanocomposite comprising an iron oxide nanoparticle core and a gold nanoparticle satellite disposed in a satellite structure on the surface of the core, comprising: a) a step of preparing a reaction solution by adding a gold precursor solution and a surface stabilizer solution to an iron oxide nanoparticle dispersion; and b) a step of lowering the temperature of the reaction solution to 0 to 20°C, adding a reducing agent solution, and ultrasonically treating.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a core-satellite nanocomposite comprising magnetic iron oxide coated with gold nanoparticles and a method for manufacturing the same. Background Technology

[0002] Iron oxide and gold nanoparticles are receiving particularly significant attention and anticipation due to their unique physical properties and versatile potential. Characterized by magnetic and optical properties, respectively, these nanoparticles can provide innovative solutions in various application fields. Iron oxide nanoparticles exhibit excellent contrast enhancement effects in magnetic resonance imaging (MRI), enabling the generation of precise and detailed images, and facilitate tissue treatment and mass delivery by utilizing magnetothermal therapy, a technology that generates heat through external alternating magnetic fields. Gold nanoparticles leverage their optical properties to detect minute changes in light and induce chemical reactions, making applications possible in diverse fields such as optical imaging and photothermal therapy. The in vivo safety and exceptional physical properties of these nanoparticles open up potential for various in vivo applications.

[0003] In particular, gold nanoparticles realize immune targets by specifically interacting with various biomolecules through gold-thiol (Au-SH) bioconjugates, which enables high-sensitivity biosensors and precise targeting of therapeutic targets in vivo. Furthermore, the surface plasmon resonance of gold nanoparticles supports the acquisition of more sophisticated information in optical analysis and imaging, and the combination of these diverse properties provides an innovative approach in the medical field. Along with this, the present invention presents a method for efficiently manufacturing nanoparticle composites by considering the properties of iron oxide nanoparticles and gold nanoparticles, and for effectively utilizing them in various application fields.

[0004] However, currently used synthesis methods for nanoparticle composites have limitations. Some small-scale synthesis methods produce nanocomposites by rapidly inducing a reaction through the addition of gold precursors and reducing agents to iron oxide nanoparticles; however, during mass production, it is difficult to control the reduction rate of the gold precursor, making it challenging to achieve uniform attachment of gold nanoparticles. Another method involves attaching a polymer to iron oxide nanoparticles to form gold nanoparticle seeds and then growing them, but this increases complexity as it requires a two-step process. Yet another method requires synthesizing iron oxide nanoparticles and gold nanoparticles separately and then attaching the two nanoparticles together.

[0005] Accordingly, there is a need for a more efficient method to mass-produce nanoparticle complexes using a more simplified approach.

[0006] Meanwhile, Korean Registered Patent Publication No. 10-2187739 is presented as a similar prior art document regarding this. Prior art literature

[0007] Korean Patent Publication No. 10-2187739 (December 1, 2020) The problem to be solved

[0008] To solve the above-mentioned problems, the present invention aims to provide a method for manufacturing a core-satellite nanocomposite that can promote mass production of the nanocomposite by controlling the reaction temperature to induce uniform growth of gold nanoparticles.

[0009] In addition, by efficiently controlling the generation and growth of nanoparticles simultaneously, it aims to ensure the uniformity of the nanocomposite and enhance the potential for commercialization of the nanocomposite in medical diagnosis, treatment, and in vivo applications.

[0010] However, the above purpose is exemplary, and the technical concept of the present invention is not limited thereto. means of solving the problem

[0011] One aspect of the present invention for achieving the above objective relates to a method for manufacturing a core-satellite nanocomposite comprising an iron oxide nanoparticle core and a gold nanoparticle satellite disposed in a satellite structure on the surface of the core, comprising: a) a step of preparing a reaction solution by adding a gold precursor solution and a surface stabilizer solution to an iron oxide nanoparticle dispersion; and b) a step of lowering the temperature of the reaction solution to 0 to 20°C, then adding a reducing agent solution and ultrasonically treating.

[0012] In one embodiment above, the gold precursor may be one or more selected from the group consisting of gold chloride, gold chloride acid, potassium gold chloride, sodium gold chloride, potassium gold bromide, sodium gold bromide, and hydrates thereof.

[0013] In one embodiment above, the concentration of the gold precursor solution may be 0.01 to 1 M, and the gold precursor may be added in an amount of 0.1 to 10 moles per mole of iron oxide nanoparticles.

[0014] In one embodiment above, the surface stabilizer may be one or more selected from the group consisting of citric acid, sodium citrate, potassium citrate, and ammonium citrate.

[0015] In one embodiment above, the concentration of the surface stabilizer solution may be 1 to 500 mM, and the surface stabilizer may be added in an amount of 0.01 to 5 moles per 1 mole of iron oxide nanoparticles.

[0016] In one embodiment above, the reducing agent may be one or more selected from the group consisting of sodium borohydride, aluminum borohydride, sodium triacetoborate, sodium hydrogen borocyanide, sodium oxalate, potassium oxalate, hydrazine, and hydroquinone.

[0017] In one embodiment above, the concentration of the reducing agent solution may be 0.01 to 1 M, and the reducing agent may be added in an amount of 0.01 to 5 moles per 1 mole of iron oxide nanoparticles.

[0018] In the above embodiment, the average diameter of the iron oxide nanoparticles may be 100 to 500 nm, and the average diameter of the gold nanoparticles may be 1 to 50 nm.

[0019] In one embodiment above, the manufacturing method may further include c) a step of separating and purifying the core-satellite nanocomposite manufactured using a magnet.

[0020] Another aspect of the present invention relates to a core-satellite nanocomposite prepared by the method for preparing the core-satellite nanocomposite described above, wherein the core-satellite nanocomposite may be a core-satellite nanocomposite having an average diameter of iron oxide nanoparticles of 100 to 500 nm and an average diameter of gold nanoparticle satellites of 1 to 50 nm.

[0021] In the other embodiment above, the core-satellite nanocomposite may have 10 or more gold nanoparticle satellites arranged on the surface of a single iron oxide nanoparticle core. Effects of the invention

[0022] A method for manufacturing a core-satellite nanocomposite according to one example of the present invention allows for the effective production of a nanocomposite having a uniform core-satellite structure even in a mass production process by appropriately controlling the reduction rate of the gold precursor when a reducing agent is added to a reaction solution containing oxidized hair nanoparticles and a gold precursor, thereby appropriately controlling the reaction temperature. Brief explanation of the drawing

[0023] FIG. 1 briefly illustrates a method for manufacturing a core-satellite nanocomposite according to an example of the present invention. Figure 2 is a scanning electron microscope (SEM) image of iron oxide nanoparticles (left) and an iron oxide nanoparticle core-gold nanoparticle satellite nanocomposite (right) according to Example 1, and the inset is a transmission electron microscope (TEM) image. Figure 3 is a graph of UV-Vis spectroscopy analysis of iron oxide nanoparticles (black solid line) and an iron oxide nanoparticle core-gold nanoparticle satellite nanocomposite (red dotted line) according to Example 1. Figure 4 is an SEM image of iron oxide nanoparticles before gold coating according to Example 1. Figure 5 is an SEM image of an iron oxide nanoparticle core-gold nanoparticle satellite nanocomposite after gold coating according to Example 1. Figure 6 is a TEM image of iron oxide nanoparticles before gold coating according to Example 1. Figures 7 and 8 are TEM images of the iron oxide nanoparticle core-gold nanoparticle satellite nanocomposite after gold coating according to Example 1, respectively. Figure 9 is an SEM image of an iron oxide nanoparticle core-gold nanoparticle satellite nanocomposite prepared by increasing the volume of each component solution according to Example 2. Figure 10 is an SEM image of an iron oxide nanoparticle core-gold nanoparticle satellite nanocomposite prepared with different gold precursor concentrations according to Examples 1, 3, and 4. Figure 11 is an SEM image of an iron oxide nanoparticle core-gold nanoparticle satellite nanocomposite prepared by adding a reducing agent solution under temperature conditions according to Comparative Example 1 (25°C) or Example 1 (10°C), respectively. Specific details for implementing the invention

[0024] The core-satellite nanocomposite comprising magnetic iron oxide coated with gold nanoparticles according to the present invention and the method for manufacturing the same will be described in detail below. The drawings presented below are provided as examples to ensure that the concept of the present invention is sufficiently conveyed to those skilled in the art. Accordingly, the present invention is not limited to the drawings presented below and may be embodied in other forms, and the drawings presented below may be exaggerated to clarify the concept of the present invention. Unless otherwise defined, technical and scientific terms used herewith have the meaning commonly understood by those skilled in the art to which this invention pertains, and descriptions of known functions and configurations that could unnecessarily obscure the essence of the present invention are omitted in the following description and accompanying drawings.

[0025] One aspect of the present invention relates to a method for manufacturing a core-satellite nanocomposite comprising an iron oxide nanoparticle core and a gold nanoparticle satellite disposed in a satellite structure on the surface of the core, comprising: a) a step of preparing a reaction solution by adding a gold precursor solution and a surface stabilizer solution to an iron oxide nanoparticle dispersion; and b) a step of lowering the temperature of the reaction solution to 0 to 20°C, then adding a reducing agent solution and ultrasonically treating.

[0026] As such, the method for manufacturing a core-satellite nanocomposite according to one example of the present invention allows for the effective production of a nanocomposite having a uniform core-satellite structure even in a mass production process by appropriately controlling the reduction rate of the gold precursor when a reducing agent is added to a reaction solution containing oxidized hair nanoparticles and a gold precursor, thereby appropriately controlling the reaction temperature.

[0027] Hereinafter, a method for manufacturing a core-satellite nanocomposite according to an example of the present invention will be described in more detail.

[0028] First, a step of preparing a reaction solution can be performed by adding a gold precursor solution and a surface stabilizer solution to an iron oxide nanoparticle dispersion.

[0029] In one example of the present invention, the iron oxide nanoparticle dispersion is a dispersion in which iron oxide nanoparticles, which are the core material of a core-satellite nanocomposite, are dispersed in a dispersion medium, and the shape and size of the iron oxide nanoparticles can be adjusted as needed. As a non-limiting example, the iron oxide nanoparticles used in the present invention may have an average diameter of 100 to 500 nm, more specifically 150 to 300 nm, and the shape may be spherical. At this time, the dispersion medium may be water such as deionized water, purified water, or distilled water, and the concentration of the iron oxide nanoparticles is not particularly limited, but specifically, for example, may be 0.01 to 50 mg / ml, more preferably 0.1 to 20 mg / ml, and even more preferably 0.3 to 10 mg / ml. In addition, to ensure that iron oxide nanoparticles are well dispersed in the dispersion medium, ultrasonic treatment can be performed for 1 to 60 minutes, and more preferably for 5 to 30 minutes.

[0030] In one example of the present invention, the gold precursor solution is a solution containing a precursor of a gold nanoparticle satellite. Specifically, for example, the gold precursor may be one or more selected from the group consisting of gold chloride, gold chloride acid, potassium gold chloride, sodium gold chloride, potassium gold bromide, sodium gold bromide, and hydrates thereof. At this time, the solvent in which the gold precursor is dissolved may be water, such as deionized water, purified water, or distilled water. The concentration of the gold precursor is not particularly limited, but specifically, for example, the concentration of the gold precursor solution may be 0.01 to 1 M, more preferably 20 to 500 mM, and even more preferably 50 to 200 mM. In addition, the amount added may be 0.1 to 10 moles per 1 mole of iron oxide nanoparticle, more preferably 0.5 to 8 moles, and even more preferably 1 to 5 moles. Nanocomposites having a core-satellite structure can be effectively manufactured within this range.

[0031] In one example of the present invention, the surface stabilizer solution is intended to stabilize the surfaces of iron oxide nanoparticles and gold nanoparticles so that a nanocomposite having a core-satellite structure can be manufactured more effectively. Specifically, for example, the surface stabilizer may be one or more selected from the group consisting of citric acid, sodium citrate, potassium citrate, and ammonium citrate. At this time, the solvent in which the surface stabilizer is dissolved may be water, such as deionized water, purified water, or distilled water. The concentration of the surface stabilizer is not specifically limited, but specifically, for example, the concentration of the surface stabilizer solution may be 1 to 500 mM, more preferably 5 to 150 mM, and even more preferably 10 to 50 mM. In addition, the amount added may be 0.01 to 5 moles per 1 mole of iron oxide nanoparticles, more preferably 0.05 to 3 moles, and even more preferably 0.1 to 1 mole. Nanocomposites having a core-satellite structure can be effectively manufactured within this range.

[0032] Once each solution is prepared in this manner, the gold precursor solution and the surface stabilizer solution can be added to the iron oxide nanoparticle dispersion, and ultrasonic treatment is performed for 5 to 100 minutes, more preferably for 10 to 60 minutes, to apply Au to the surface of the iron oxide nanoparticles 3+ It is possible to make ions attach.

[0033] Next, the temperature of the reaction solution can be lowered using an ice bath or the like, and the reaction temperature can be 0 to 20°C, or more preferably 5 to 15°C. Within this range, the reduction rate of the gold precursor can be appropriately controlled, allowing a nanocomposite with a uniform core-satellite structure to be formed even in a mass production process. On the other hand, if the reaction temperature exceeds 20°C, the reduction reaction of the gold precursor is induced rapidly, which may result in the gold nanoparticle satellites not being uniformly formed on the core of the iron oxide nanoparticles during mass production. If the reaction temperature is below 0°C, it may induce cooling of the solvent (water), which not only leads to a decrease in the reaction but also slows down the reaction rate, thereby inducing a decrease in the growth of the gold nanoparticle satellites.

[0034] After the reaction temperature is adjusted to 0 to 20°C, a reducing agent solution may be added to the reaction solution. At this time, as gold seeds are formed immediately upon adding the reducing agent solution and turn dark red, it is desirable to perform ultrasonic treatment quickly after injecting the reducing agent, and the ultrasonic treatment may be performed for 1 to 30 seconds, or more preferably 3 to 20 seconds.

[0035] Meanwhile, the above reducing agent solution is Au attached to the surface of iron oxide nanoparticles 3+The purpose is to form gold nanoparticle satellites on the surface of an iron oxide nanoparticle core by reducing ions. Specifically, for example, the reducing agent may be one or more selected from the group consisting of sodium borohydride, aluminum borohydride, sodium triacetoborate, sodium hydrogen borocyanide, sodium oxalate, potassium oxalate, hydrazine, and hydroquinone. At this time, the solvent in which the reducing agent is dissolved may be water, such as deionized water, purified water, or distilled water. The concentration of the reducing agent is not specifically limited, but specifically, for example, the concentration of the reducing agent solution may be 0.01 to 1 M, more preferably 20 to 500 mM, and even more preferably 50 to 200 mM. In addition, the amount added may be 0.01 to 5 moles per 1 mole of iron oxide nanoparticle, more preferably 0.05 to 3 moles, and even more preferably 0.1 to 1 mole. Au attached to the surface of iron oxide nanoparticles within this range 3+ Ions are effectively reduced, allowing for the effective fabrication of nanocomposites having a core-satellite structure.

[0036] In the core-satellite nanocomposite prepared by the above steps, the average diameter of the gold nanoparticle satellite may be 1 to 50 nm, more specifically 3 to 40 nm, and even more specifically 5 to 30 nm, but is not necessarily limited thereto.

[0037] Furthermore, a method for manufacturing a core-satellite nanocomposite according to an example of the present invention may further include c) a step of separating and purifying the manufactured core-satellite nanocomposite using a magnet.

[0038] Since the core of the above core-satellite nanocomposite is iron oxide, the nanocomposite can be separated using a magnet without any separate separation process, and then the core-satellite nanocomposite can be obtained by washing with water such as deionized water, purified water, or distilled water and drying.

[0039] In addition, another aspect of the present invention relates to a core-satellite nanocomposite prepared by the method for preparing the core-satellite nanocomposite described above, wherein the core-satellite nanocomposite may be a core-satellite nanocomposite having an average diameter of iron oxide nanoparticles of 100 to 500 nm and an average diameter of gold nanoparticle satellites of 1 to 50 nm.

[0040] As a more specific example, the iron oxide nanoparticles may have an average diameter of 100 to 500 nm, more specifically 150 to 300 nm, and their shape may be spherical. Additionally, the average diameter of the gold nanoparticle satellite may be 1 to 50 nm, more specifically 3 to 40 nm, and even more specifically 5 to 30 nm, but is not necessarily limited thereto.

[0041] In addition, the core-satellite nanocomposite may have 10 or more gold nanoparticle satellites arranged on the surface of a single iron oxide nanoparticle core, more specifically, 10 to 50, and more preferably 10 to 30 gold nanoparticle satellites arranged. On the other hand, unlike the method of manufacturing the core-satellite nanocomposite described above, the core-satellite nanocomposite manufactured by adding a reducing agent solution at a temperature of 25°C or higher may not have gold nanoparticle satellites uniformly formed on the iron oxide nanoparticle core during mass production because the reduction reaction of the gold precursor is rapidly induced, and the number of gold nanoparticle satellites may be less than 10 due to the low frequency of gold seed generation.

[0043] Hereinafter, the core-satellite nanocomposite comprising magnetic iron oxide coated with gold nanoparticles according to the present invention and the method for manufacturing the same will be described in more detail through examples. However, the following examples are merely references for explaining the present invention in detail, and the present invention is not limited thereto and can be implemented in various forms.

[0044] Furthermore, unless otherwise defined, all technical and scientific terms have the same meaning as generally understood by one of the art to which the present invention pertains. The terms used in the description herein are merely for the purpose of effectively describing specific embodiments and are not intended to limit the present invention. Additionally, units of additives not specifically stated in the specification may be in weight percent.

[0045] [Example 1]

[0046] 1 mg of iron oxide (Fe3O4) nanoparticles was dispersed in 1 mL of deionized water (DIW), followed by sonication for 10 minutes to ensure the nanoparticles were thoroughly dispersed within the solution. To this iron oxide nanoparticle dispersion, 100 µL of an aqueous HAuCl4·3H2O solution (concentration 25 mM) and 100 µL of an aqueous trisodium citrate solution (concentration 20 mM) were added, and sonication was performed for 30 minutes to [prepare] Au 3+ Ions were allowed to attach to the surface of iron oxide nanoparticles. Then, the temperature of the reaction solution was lowered to 10°C, 20 µl of an aqueous NaBH4 solution (concentration 100 mM) was added, and the solution was sonicated for 30 minutes. Immediately after the addition of NaBH4, Au seeds were formed in the reaction solution, causing it to turn dark red.

[0047] After the reaction was finished, the final product was washed three times with deionized water using magnetic separation, and then dried in a vacuum oven at 60°C for 6 hours.

[0048] [Example 2]

[0049] As shown in Table 1 below, the concentration of each solution was the same as in Example 1, but the amount of solution added was increased by 2, 3, and 10 times, respectively, to prepare the core-satellite nanocomposite, and all other processes were carried out in the same manner as in Example 1.

[0050] Iron oxide nanoparticle dispersion HAuCl4·3H2O aqueous solution trisodium citrate solution NaBH4 aqueous solution 2 times 200 ㎕(1 ㎎ / ㎖) 200 µl (25 mM) 200 µl (25 mM) 40 µl (100 mM) 3 times 300 ㎕(1 ㎎ / ㎖) 300 µl (25 mM) 300 µl (25 mM) 60 µl (100 mM) 10 times 1 ㎖(1 ㎎ / ㎖) 1 ml (25 mM) 1 ml (25 mM) 200 µl (100 mM)

[0051] [Example 3]

[0052] All procedures were carried out in the same manner as in Example 1, except that 100 µl of an aqueous solution of HAuCl4·3H2O (concentration 20 mM) was used.

[0053] [Example 4]

[0054] All procedures were carried out in the same manner as in Example 1, except that 100 µl of an aqueous solution of HAuCl4·3H2O (concentration 30 mM) was used.

[0055] [Comparative Example 1]

[0056] All processes were carried out in the same manner as in Example 1, except that the temperature of the reaction solution was 25℃.

[0057] [Analysis of Characteristic Evaluation Results]

[0058] Figure 2 is a scanning electron microscope (SEM) image of iron oxide nanoparticles (bare Fe3O4NC) before gold coating according to Example 1 (left) and a gold-coated iron oxide nanoparticle core-gold nanoparticle satellite nanocomposite (right), and the inset is a transmission electron microscope (TEM) image. In particular, by referring to the TEM image, it can be confirmed that gold nanoparticle satellites are attached to the surface of the iron oxide nanoparticles.

[0059] Figure 3 is a UV-Vis spectroscopy analysis graph of iron oxide nanoparticles before gold coating (black solid line) and a gold-coated iron oxide nanoparticle core-gold nanoparticle satellite nanocomposite (red dotted line) according to Example 1, where the plasmon resonance peak appearing around 550 nm wavelength indicates the formation of gold nanoparticles, and the broad peak appearing around 400 nm wavelength originates from Fe3O4 nanoparticles.

[0060] Figures 4 to 8 are SEM and TEM images of iron oxide nanoparticles before gold coating and gold-coated iron oxide nanoparticle core-gold nanoparticle satellite nanocomposites according to Example 1, respectively, and it can be confirmed that gold nanoparticle satellites are attached to the surface of the iron oxide nanoparticles.

[0061] Figure 9 is an SEM image of an iron oxide nanoparticle core-gold nanoparticle satellite nanocomposite prepared by increasing the volume of each component solution according to Example 2, and it can be confirmed that gold nanoparticle satellites are uniformly attached to the surface of the iron oxide nanoparticle core even after the volume increase.

[0062] Figure 10 is an SEM image of iron oxide nanoparticle core-gold nanoparticle satellite nanocomposites prepared with different gold precursor concentrations according to Example 1, Example 3, and Example 4. It can be seen that gold nanoparticle satellites are attached to the surface of iron oxide nanoparticles in all nanocomposites, and in particular, in the case of Examples 1 and 4, where the concentration of the gold precursor is 25 mM or higher, the frequency of gold nanoparticle satellites is higher compared to Example 3.

[0063] Figure 11 is an SEM image of an iron oxide nanoparticle core-gold nanoparticle satellite nanocomposite prepared by adding a reducing agent solution at temperatures of 25°C or 10°C, respectively. In the case of Comparative Example 1, in which the reaction was carried out at a temperature of 25°C or higher, it can be seen that the size of the gold nanoparticle satellites is somewhat non-uniform and the gold nanoparticle satellites are not uniformly attached.

[0064] Although the present invention has been described above through specific details and limited embodiments, this is provided merely to aid in a more comprehensive understanding of the invention, and the invention is not limited to the above embodiments. Those skilled in the art can make various modifications and variations from this description.

[0065] Accordingly, the scope of the present invention is not limited to the described embodiments, and all things equivalent to or having equivalent variations to the claims set forth below, as well as the claims set forth below, shall be considered to fall within the scope of the concept of the present invention.

Claims

Claim 1 A method for manufacturing a core-satellite nanocomposite comprising an iron oxide nanoparticle core and a gold nanoparticle satellite disposed in a satellite structure on the surface of the core, comprising: a) a step of preparing a reaction solution by adding a gold precursor solution and a surface stabilizer solution to an iron oxide nanoparticle dispersion and ultrasonically treating; and b) a step of lowering the temperature of the reaction solution to 0 to 20°C, adding a reducing agent solution, and ultrasonically treating; wherein the surface stabilizer is one or more selected from the group consisting of citric acid, sodium citrate, potassium citrate, and ammonium citrate, the surface stabilizer solution has a concentration of 5 to 150 mM, the average diameter of the iron oxide nanoparticle is 150 to 300 nm, and the average diameter of the gold nanoparticle satellite is 3 to 40 nm. Claim 2 A method for manufacturing a core-satellite nanocomposite according to claim 1, wherein the gold precursor is one or more selected from the group consisting of gold chloride, gold chloride acid, potassium gold chloride, sodium gold chloride, potassium gold bromide, sodium gold bromide, and hydrates thereof. Claim 3 A method for manufacturing a core-satellite nanocomposite according to claim 2, wherein the concentration of the gold precursor solution is 0.01 to 1 M. Claim 4 A method for preparing a core-satellite nanocomposite according to claim 2, wherein the gold precursor is added in an amount of 0.1 to 10 moles per 1 mole of iron oxide nanoparticles. Claim 5 delete Claim 6 delete Claim 7 A method for manufacturing a core-satellite nanocomposite according to claim 1, wherein the surface stabilizer is added in an amount of 0.01 to 5 moles per 1 mole of iron oxide nanoparticles. Claim 8 A method for preparing a core-satellite nanocomposite according to claim 1, wherein the reducing agent is one or more selected from the group consisting of sodium borohydride, aluminum borohydride, sodium triacetoborate, sodium hydrogen borocyanide, sodium oxalate, potassium oxalate, hydrazine, and hydroquinone. Claim 9 A method for manufacturing a core-satellite nanocomposite according to claim 8, wherein the concentration of the reducing agent solution is 0.01 to 1 M. Claim 10 A method for preparing a core-satellite nanocomposite according to claim 8, wherein the reducing agent is added in an amount of 0.01 to 5 moles per 1 mole of iron oxide nanoparticles. Claim 11 delete Claim 12 A method for manufacturing a core-satellite nanocomposite according to claim 1, wherein the manufacturing method further comprises: c) a step of separating and purifying the core-satellite nanocomposite manufactured using a magnet. Claim 13 A core-satellite nanocomposite prepared by a method for preparing a core-satellite nanocomposite selected from any one of claims 1 to 4, 7 to 10, and 12, wherein the core-satellite nanocomposite has an average diameter of iron oxide nanoparticles of 150 to 300 nm and an average diameter of gold nanoparticle satellites of 3 to 40 nm. Claim 14 In claim 13, the core-satellite nanocomposite is a core-satellite nanocomposite in which 10 or more gold nanoparticle satellites are disposed on the surface of a single iron oxide nanoparticle core.